Professional services leadership handbook : how to lead a professional services firm in a new age of competitive disruption /: how to lead a professional services firm in a new age of competitive disruption. (2017) - (Marketing executive), Clark, Nigel; Kent, Ben; Beddow, Alastair; Furner, Adrian
No abstract available